Navigating Compliant Agency in Cyberspace: Muslim Womanhood Through the Lens of Oki Setiana Dewi - Asya Dwina Luthfia (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2024)
In contrast to the stereotype that docile Muslim women are confined to domestic roles, this study examines how Muslim womanhood can balance economic independence with adherence to religious and societal expectations. Focusing on the case of Indonesian ustadzah (Islamic preacher) Oki Setiana Dewi, this research explored her agency as expressed through her Instagram activity. Cultivating the compliant agency, this article asserts that consciously adhering to religious values preserves patriarchal expectations while gaining authority and financial freedom. This study utilized qualitative content analysis, collecting data from Oki’s Instagram account using "Instalouder" and analyzing captions with "Voyant Tools" to identify recurring themes. Oki's persona conforms to what society expects of women. She portrays herself as a devout Ustadzah, a prosperous entrepreneur, and a mother who is dedicated to her kids. This illustrates cyberspace as a place where women preserve traditional norms as well as a space for them to express their agency. It fosters a duality of cyberspace that is both empowering and constraining. This raises critical issues that Oki's narrative, while seemingly empowering, reinforces patriarchal norms that confine women to domestic and religious obligations, even to their agency. In other words, her portrayal emphasizes the ability to balance public and private roles but leaves room for questioning the societal structures that enforce these expectations. It raises critical questions about whether such an agency disrupts or perpetuates systemic inequalities in Indonesia's gendered social landscape.